Nigerian students' perception of Student-Centered Learning (SCL) - Bolanle, Jimoh Taibat (2010)
The Nigerian formal education has long been dominated by the traditional lecture method where the lecturer or professor impart knowledge to the passive learners through oratories; which makes students to be passive recipients of information and thus memorizes facts for tests and examinations. Thus, there is a need to study the perception of Nigerian students about the learning approach to pave way for successful implementation of Student Centered Learning (SCL) curriculum in the Nigerian education system. Therefore, this study aims at carrying out the perception study among Nigerian students in some Malaysian public Universities about the SCL approach in terms of the perceived benefits and satisfaction. The study was conducted among 222 students from four public Universities in Malaysia using questionnaire as the survey instrument which was developed for the two constructs (perception (benefits) and satisfaction). The data was analyzed using descriptive statistics. The findings of the study showed that the surveyed students perceived SCL to be of great advantages in their learning process and they also feel satisfied with the approach most especially the collaborative form of SCL. It is recommended that future studies should expand the coverage and also investigate the implications of the approach on both the teachers and students.